THE CONTROL OF THE ACTIVE ELECTRIC POWER CONSUMED BY METAL - CUTTING LATHES DRIVE - D.V. MARKARIAN; J.A. TRINZ (Вестник Донского государственного технического университета, 2018)
The highly precise control device of active electric power consumed by metal -cutting lathes drives is described.